An algorithm for the typing of enteroviruses and correlation to serotyping by viral neutralization - Kiang, David; Newbower, Elly Chou; Yeh, Elaine; Wold, Lauren; Chen, Lily; Schnurr, David P. (Journal of clinical virology, 2009)
Human enteroviruses (HEVs) are common pathogens which cause a broad spectrum of illnesses ranging from asymptomatic infection to acute myocarditis and aseptic meningitis. The neutralization assay for serotype determination is labor-intensive and time-consuming. There is a need for a methodology that is more rapid and widely accessible. Our goals were to develop an algorithm to type enteroviruses which combines both serologic typing, based on indirect immunofluorescence assay (IFA) using type-specific monoclonal antibodies (mAbs) and genotyping, by DNA sequence analysis and to assess the correlation of both IFA and genotyping to traditional viral neutralization by type-specific antisera. Clinical specimens initially determined to be enterovirus positive by nucleic acid detection were grown in cell culture and typed using mAbs. Specimens that could not be typed by mAbs were subject to molecular analysis. Genotyping was performed by a combination of either a primary or semi-nested RT-PCR for a region within VP3/VP1 and followed by direct DNA sequencing of PCR products. Database homology comparisons and phylogenetic analysis were performed based on a defined region (303 nt) within the VP1 gene. We inoculated 134 enterovirus nucleic acid amplification-positive specimens into culture and 115 (86%) of these isolates were successfully typed by this algorithm. We have demonstrated a strong correlation between serotyping by viral neutralization to both IFA by type-specific mAbs and genotyping. Typing of human enteroviruses can be effectively performed using an integration of antibody-based and molecular methods.